شرحِ حدیث میں سنن ابوداؤ د کے مختلف نسخوں سے استفادہ (مولانا خلیل احمد سہارن پوری کی بذل المجہودکا خصوصی مطالعہ): Role of Different Manuscripts of Sunan Abu Dawood for Profound Elucidation with Special Reference to Badhl al-Majhood by Maulana Khalil Ahmad Saharanpuri - Dr. Muhammad Haroon; Dr.Muhammad Feroz-ud-Din Shah (MEI, 2024)
Sunan Abu Dawood enjoys great popularity in the books of Hadith due to its reliability. As a result, scholars have written numerous commentaries on it, both among Arab scholars and those from the Indian subcontinent. One such notable figure from the subcontinent is Maulana Khalil Ahmad Saharanpuri, who authored a detailed commentary titled "Badhl al-Majhud fi hall e Sunan Abi Dawud" spanning fourteen volumes. This work has been highly regarded by scholars of the Hanafi school of thought. This book has remained a focal point of attention for scholars due to its distinctive features. One notable characteristic of this book is that the esteemed authors critically examine various versions of the explanation during the commentary of Sunan Abi Dawood. Differences between versions sometimes affect the status of the Hadith, which they particularly address. In such cases, if reconciling different versions does not resolve the issue, they resort to utilizing narrations from other sources that closely resemble the Hadith in question.Sometimes, in the name of the narrator or in the commentary provided by Imam Abu Dawood at the end of the Hadith, there are variations in wording. Maulana Saharanpuri, while acknowledging the differences among versions, provides his commentary and expresses his opinion. In some versions, discrepancies are also found in the translation of chapter headings; a Hadith may appear under one chapter in one version and under a different chapter in another. In such cases, Maulana Saharanpuri clarifies the original position of the Hadith to determine which chapter's heading suits it best.